PENGARUH KEUANGAN DAERAH TERHADAP PDRB DENGAN BELANJA DAERAH SEBAGAI VARIABEL INTERVENING DI PROVINSI JAWA TIMUR - Endang Setiati, 11.42.02.0002 (Students Journal of Economic and Management, 2013)
The purpose of the reform is to increase the independence of the region with reduce fiscal dependence on central government The size of the revenue affects the size of expenditure the area. While government consumption to be one of the elements contributing to Gross Regional Domestic Product, which is one indicator of the success of development in the area. The empirical study is to describe the relationship among Local Taxes, Local Retribution, Revenue Sharing Grant and General Allocation Grant to the Gross Regional Domestic Product directly or indirectly by Local Expenditure as a intervening variable. The sample used in this study were 38 districts / cities in East Java province using 2004 up to 2010 data. The study used Fixed Effect Method â Cross Section Weight with Eviews program. The results showed that the Local Taxes, General Allocation Grant, Revenue Sharing Grant and Local Expenditure positively influences the Gross Regional Domestic Product, but Local Retribution has a negative influence. Local Expenditure doesnât have the function of mediating variables. Keywords: Â Â Â  Local Taxes, Local Retribution, Revenue Sharing Grant, General Allocation Grant, Local Expenditure and Gross Regional Domestic Product.